GAYA INTERIOR RUMAH DINAS BUPATI BLITAR - Attamami, Mohammad Nur Farchan; Budiwiyanto, Joko (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2020)
The research entitled Interior Style of the Blitar Regent's Official House aims to determine the interior style of the house. Blitar was originally the kingdom of the Surakarta Sunanate. In 1830, the Surakarta Sunanate began to hand over Blitar to the Dutch as a consequence of Dutch assistance to the Kasunanan after the end of the Diponegara War. The Dutch government subsequently appointed a new regent as the ruler of Blitar complete with government support facilities, including the regent's official residence. The uniqueness of the official residence of the Blitar Regent is that it was built by combining the Surakartanan and Dutch styles to produce a new interior style. To achieve the goal, a descriptive qualitative research method is used with an interior style approach. The sources used in this research are sources, literature data, places/buildings, and pictures. The interior of the Blitar Regent's official residence is a combination of Javanese style and Dutch style called Indis style. The application of the Javanese style can be found in the arrangement of spaces, space zoning, and direction towards space. From a visual point of view, the Javanese style is more prominent in the front room area, especially the pendapa with the form of an open space composed of saka and the use of Javanese-style ornaments. The Indies style is more prominent in the main house area. Indische style in the main house can be seen from the space plan and the elements that form the space, especially the pillars lining the veranda area and the shape of the towering buildings. The Javanese style that appears on the front is the government's attempt at that time to show that Blitar is still part of Javanese society, especially the Surakarta Sunanate Kingdom. The colonial-style manifestation of the main house was an attempt by the Colonial government to show that the Blitar government was under the control of the colonial government at that time. AbstrakPenelitian dengan judul Gaya Interior Rumah Dinas Bupati Blitar bertujuan untuk mengetahui gaya interior pada rumah tersebut. Blitar pada awalnya merupakan wilayah kerajaan Kasunanan Surakarta. Pada tahun 1830, Blitar mulai diserahkan oleh Kasunanan Surakarta kepada Belanda sebagai konsekuensi atas bantuan Belanda kepada Kasunanan setelah berakhirnya Perang Diponegara. Pemerintah Belanda selanjutnya mengangkat bupati baru sebagai penguasa Blitar lengkap beserta fasilitas pendukung pemerintahan, di antaranya adalah rumah dinas bupati. Keunikan rumah dinas Bupati Blitar adalah dibangun dengan menggabungkan gaya Surakartanan dan Belanda sehingga menghasilkan gaya interior baru. Untuk mencapai tujuan digunakan metode penelitian kualitatif deskriptif dengan pendekatan gaya interior. Sumber-sumber yang digunakan dalam penelitian ini adalah narasumber, data literatur, tempat/bangunan, dan gambar. Interior rumah dinas Bupati Blitar merupakan gabungan gaya Jawa dan gaya Belanda yang disebut gaya Indis. Penerapan gaya Jawa terdapat pada susunan ruang, zonasi ruang, serta arah hadap ruang. Dari segi visual gaya Jawa lebih menonjol pada area ruang depan terutama pendapa dengan bentuk ruang terbuka yang disusun oleh saka-saka serta digunakannya ornamen-ornamen bergaya Jawa. Adapun gaya Indis lebih menonjol pada area rumah Induk. Gaya Indis pada rumah Induk dapat dilihat dari denah ruang serta elemen pembentuk ruang, terutama adanya pilar-pilar yang berjajar di area beranda (teras) serta bentuk bangunan yang tinggi menjulang. Gaya Jawa yang nampak di bagian depan merupakan usaha pemerintah pada masa itu untuk menunjukkan bahwa Blitar masih bagian dari masyarakat Jawa, khususnya Kerajaan Kasunanan Surakarta. Wujud gaya Kolonial pada rumah induk merupakan usaha pemerintah Kolonial untuk menunjukkan bahwa pemerintah Blitar berada dalam kendali pemerintah kolonial pada masa tersebut.